Handbook on measurement, assessment, and evaluation in higher education - Secolsky, Charles; Denison, D. Brian (New York Routledge,Francis Group, 2018)
Increased demands for colleges and universities to engage in outcomes assessment for accountability purposes have accelerated the need to bridge the gap between higher education practice and advances in the fields of measurement, assessment and evaluation. This research handbook provides higher education administrators, student affairs personnel, institutional researchers and faculty with an integrated volume of theory, method and application
Part I: Measurement, assessment, and evaluation in higher education: past, present, and future -- Part II: Assessment and evaluation in higher education -- Part III: Theoretical Foundations of Educational Measurement -- Part IV: Testing and assessment: implications for decision-making -- Part V: Test construction and development -- Part VI: Statistical approaches in higher education measurement, assessment, and evaluation -- Part VII: Approaches to evaluation in higher education -- Part VIII: Approaches to assessment in higher education -- Part IX: Issues in assessment and evaluation in higher education.
Includes bibliographical references and index.
Keywords: Education, Higher -- Evaluation -- Handbooks, manuals, etc; Educational tests and measurements -- Handbooks, manuals, etc